Analysis Of Employee Spirit In View From Work Environment And Communication (Case Study in the Production Section of PT. Goenoeng Poetri Lestari) - Sintia, Elis; Yusnita, Rita Tri; Barlian, Barin (Universitas Dehasen Bengkulu, 2024)
Morale is often associated with the attitude or behavior of employees towards the work they do by paying attention and observing the attitudes and behavior of employees towards their work. This study aims to determine the effect simultaneously or partially of the Work Environment and Communication variables on Work Enthusiasm. The population used in this study were 448 production employees at PT. Goenoeng Poetri Lestari. The method used in this research is descriptive research with a quantitative approach. The sample selection uses a random sample. The sample used is using a random sampling sample, namely 211 employees of the production division of PT. Goenoeng Poetri Lestari. Sources of data in this study are secondary data and primary data. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the results of the study it is concluded that the Work Environment and Communication simultaneously have a significant effect on Work Morale. The work environment partially has a significant effect on work morale. Communication partially has a significant effect on morale.